The COVID-19 Outbreak and Subjects With Mental Disorders Who Presented to an Italian Psychiatric Emergency Department. Issue 4 (19th April 2021) - Montalbani, Benedetta; Bargagna, Paride; Mastrangelo, Martina; Sarubbi, Salvatore; Imbastaro, Benedetta; De Luca, Gabriele Pasquale; Anibaldi, Gaia; Erbuto, Denise; Pompili, Maurizio; Comparelli, Anna
Abstract: We performed a retrospective study from January to May 2020 to establish the sociodemographic and clinical characteristics of patients with mental health problems who arrived at an Italian emergency department during the COVID-19 outbreak. We divided the sample into two groups taking as a watershed March 11, when the World Health Organization announced COVID-19 outbreak as a pandemic. Chi-square/ t -tests, adjusted p values (Bonferroni method), and regression analysis were performed. Patients who arrived at the emergency department during the lockdown decreased by 56%; showed greater active suicidal ideation, more tension, and more severe psychopathological state; were living alone more frequently; and were taking home treatment mainly based on second-generation antipsychotics. According to our study, it seems that patients with mental disorders have consulted psychiatric services less frequently during the pandemic, but the economic, health, and social distress may be linked with an increase in suicidal risk and the severity of the psychopathological state.